Proteínas c reactiva en niños menores de 5 años con faringoamigdalitis del sector barrio lindo cantón Babahoyo, Los Ríos primer semestre del 2015 - García Mendoza, Loida Elizabeth (2015)
The sore throat in children is one of the most common infectious diseases in the doctor's family. The most frequent etiology is viral. Within the bacterial etiology, the main responsible agent is Streptococcus pyogenes, cause of 5-30% of cases. The application for review of PCR, called analysis of protein C, is a good aid since it allows to know the infectious or inflammatory by the levels that present the patient, applying this technique may reduce transmission time and prevent suppurative complications local and non-suppurative. C-reactive protein (CRP) (CRP for its acronym in English) is a plasma protein that is located in the blood - arising in the acute phase of general body inflammatory disease, is produced by the liver and it seems, that their level rises when there is inflammation throughout the body, or in a considerable part of it. C-reactive protein verifies if there is inflammation throughout the body. It is not that this is a very specific parameter; i.e., it can reveal that we are suffering from an inflammation somewhere in the body, but it does not have the ability to provide us with the exact location. It should take into account that it is not 100% reliable marker already that a CRP level low do not always mean to be missing an inflammation, in addition the CRP levels may not be elevated in people with rheumatoid arthritis and lupus, the truth is that the reason for this remains unknown. It is demonstrated in this research is that the C-reactive protein test should be recommended to check if the patient suffers from inflammatory disease sore throat, either to determine if an anti-inflammatory chemical recommended is working.